Anticancer Activities and Metabolite Profiling of UHPLC-HRMS Method from Chrysanthemum x morifolium (Ramat.) Hemsl Leaves - Maesaroh, Imas; Barliana, Melisa Intan; Abdulah, Rizky; Muhaimin, Muhaimin (Bogor Agricultural University, Indonesia, 2026)
The Chrysanthemum morifolium Ramat, traditionally used for cancer treatment, including breast cancer, possesses anticancer properties. The aim of this study is metabolite profiling using ultra-high-performance liquid chromatography in conjunction with the high-resolution mass spectrometry (UHPLC-HRMS) technique and its correlation with the cytotoxic activity of the extract and ethyl acetate fraction of Chrysanthemum x morifolium (Ramat.) Hemsl leaves on cancer cells. The ethyl acetate fraction from the hydrolyzed ethanol extract of (Chrysanthemum x morifolium (Ramat.) Hemsl) leaves has anticancer activity against the MCF-7 breast cancer cells. Metabolite profiling was used to understand the presence of metabolites that have anticancer activity. UHPLC-HRMS was used to profile their metabolites. Compound Discoverer 3.3 software finished data processing and metabolite annotation. Anticancer activity was performed using the 2-[2-methoxy-4-nitrophenyl]-3[4-nitrophenyl]-5[2,4-disulfophenyl]-2H-tetrazolium (WST-8) assay. As many as 57 secondary metabolites were identified by UHPLC-HRMS analysis. Secondary metabolites that have the potential as anti-breast cancer are glycitein, diosmetin, kaempferol, esculetin, scopoletin, dihydroartemisinin, and Chrysin, with successive percentages of 31.39%, 19.91%, 5.61%, 2.63%, 0.82%, 0.14%, and 0.05%. Ethyl acetate fraction showed stronger cytotoxic activity than ethanol extract against MCF-7 cells with IC50 values of 66.31 ppm at 24 hours incubation and 40.35 ppm at 48 hours. Further research can be conducted on the isolation of flavonoids from the ethyl acetate fraction, as well as the analysis of cell cycle apoptosis stimulation and gene expression mechanisms.